Wheel Bug, Arilus cristatus (Linnaeus) (Insecta: Hemiptera: Reduviidae) - Frank W. Mead (EDIS, 2002)
The wheel bug, Arilus cristatus (Linnaeus), is a moderately common, widely distributed, beneficial assassin bug that preys on pest insects. However, its bite can be more severe than a bee sting, and both nymphs and adults should be avoided or handled with caution. This document is EENY-086 (originally published as DPI Entomology Circular No. 143), one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: June 1999.